2022
DOI: 10.3390/app12126219
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pulsed Electric Field and Ultrasound in the Extraction of Polyphenols and Volatile Compounds from Grape Stems

Abstract: Increasing the yield of extraction of bioactive compounds from plants is of high importance. Grape stems are widely discarded during the wine-making process, despite their high content in many valuable compounds. The aim of this work was to examine whether the use of pulsed electric field (PEF) treatment of the stems could increase the yield of polyphenol and volatile compounds in the extracts. For this reason, a relatively low-energy consuming PEF process was employed (low-electric field strength, 1 kV/cm) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Görgüç et al [ 201 ] applied PEF + UAE to extract polyphenols from the Rosemary byproduct ( Table 3 ) and reported that UAE + PEF (2.97 mg GAE/g) was 1.5× higher than UAE alone. Likewise, Ntourtoglou et al [ 202 ] extracted polyphenols from grape stems ( Table 3 ) and reported that PEF-UAE augmented the TPC extraction (35%) compared to the control (PEF alone). This could be explained by the combinative effect of the electroporation by (PEF) and the cavitation effect by ultrasound that cleaves the cell membrane and allows polyphenols to be released, thus increasing the TPC yield.…”
Section: Integrations Of Avant-garde Extraction Technologiesmentioning
confidence: 99%
“…Görgüç et al [ 201 ] applied PEF + UAE to extract polyphenols from the Rosemary byproduct ( Table 3 ) and reported that UAE + PEF (2.97 mg GAE/g) was 1.5× higher than UAE alone. Likewise, Ntourtoglou et al [ 202 ] extracted polyphenols from grape stems ( Table 3 ) and reported that PEF-UAE augmented the TPC extraction (35%) compared to the control (PEF alone). This could be explained by the combinative effect of the electroporation by (PEF) and the cavitation effect by ultrasound that cleaves the cell membrane and allows polyphenols to be released, thus increasing the TPC yield.…”
Section: Integrations Of Avant-garde Extraction Technologiesmentioning
confidence: 99%
“…Ntourtoglou et al [67] examined the potential impact of PEF pretreatment on the efficiency with UAE of polyphenols and volatile compounds from grape stems. An electric field strength of 1 kV/cm for a total duration of 30 min was used.…”
Section: Grapesmentioning
confidence: 99%
“…61 Turk et al 62 reported that the PEF application increased the odor density in apple juice. Intense feeling of odor depending on the improved aroma extraction with the PEF application 63 may have caused the odor score of the PEF-treated shalgam juice samples. However, statistically no difference in the odor score between the samples was observed on the 60th day (P > 0.05).…”
Section: Sensorial Characteristicsmentioning
confidence: 99%